Modification of method of histological investigation of bone tissue. - Pikalyuk, V. S.; Kutya, S. A.; Shaduro, D. V. (Морфологія / Morphologia / Morfologìâ, 2010)
Article contains description of method of undecalcified sections preparation, staining with following morphometry.